INTEGRASI DATA EKONOMI ANTAR LEMBAGA UNTUK MENINGKATKAN EFISIENSI KEBIJAKAN PUBLIK - Alfa Rizi Azhari; Muhammad Irwan Padli Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Economic data integration between institutions is a crucial element in realizing efficient, targeted, and evidence-based public policies. This study uses a descriptive qualitative approach to examine the actual conditions of economic data integration in Indonesia, the challenges faced, and its impact on the efficiency of public policies. Data were obtained through in-depth interviews with informants from various government agencies and studies of related policy documents. The results of the study show that despite the existence of national policies such as One Data Indonesia, data integration has not been running optimally due to technical constraints, low institutional coordination, and inadequate regulations and supporting infrastructure. As a result, public policies are often inefficient and less responsive to actual needs. These findings emphasize that successful data integration requires cross-sector synergy, strengthening data governance, and ongoing political commitment.